(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the use of linguistic devices in literary texts, their poetic actualization, integrative relations within the text, and the aesthetic function of language units from a lingvopoetic perspective. Through examples, the artistic and aesthetic significance of phono-graphic tools is revealed. It is scientifically substantiated that not all linguistic units within a text possess the same aesthetic status, and their functional load in poetic context varies.